Prostaglandin E2 Signals Through E Prostanoid Receptor 2 to Inhibit Mitochondrial Superoxide Formation and the Ensuing Downstream Cytotoxic and Genotoxic Effects Induced by Arsenite - Cerioni, Liana; Guidarelli, Andrea; Fiorani, Mara; Cantoni, Orazio (Frontiers in Pharmacology, 2019)
We investigated the effects of prostaglandin E2 (PGE2), an important inflammatory lipid mediator, on the cyto-genotoxicity induced by arsenite. Using a toxicity paradigm in which the metalloid uniquely induces mitochondrial superoxide (mitoO2-.) formation, PGE2 promoted conditions favouring the cytosolic accumulation of Bad and Bax, abolished mitochondrial permeability transition (MPT) and the ensuing lethal response through an E prostanoid receptor 2/adenylyl cyclase/protein kinase A (PKA) dependent signalling. It was however interesting to observe that, under the same conditions, PGE2 also abolished the DNA-damaging effects of arsenite and that this response was associated to an unexpected suppression of mitoO2-. formation. We conclude that PGE2 promotes PKA-dependent inhibition of mitoO2-. formation, thereby blunting the downstream responses mediated by these species, leading to DNA strand scission and MPT-dependent apoptosis. These findings are therefore consistent with the possibility that, in cells responding to arsenite with mitoO2-. formation, PGE2 fails to enhance -but rather decreases- the risk of neoplastic transformation associated with genotoxic events.